The Sea-Based Waste Collection Routing Problem Using a Novel Value Recovery Function - Ricardo C. Alindayu II; Jayne Lois San Juan; Charlle L. Sy (Chemical Engineering Transactions)
The Asia-Pacific region has been implicated as a major hotspot for plastic pollution in the world’s oceans, causing environmental and economic damage to marine ecosystems and maritime industries. In response to this challenge, cleaning vessels have been optimized to collect floating plastic waste before retrieval becomes more costly and difficult. However, prior vessel routing optimization studies focused solely on cost minimization without considering the yield of collected plastic waste critical to the goal of plastic elimination from the oceans. As such, a mixed-integer linear programming model called the sea-based waste collection routing problem was developed to maximize value recovery through a novel profit function. Two computer-generated instances with differing node sizes were used to illustrate the functionalities of the SB-WCRP. A modified ant colony optimization algorithm was constructed to arrive at near-optimal solutions within a reasonable computing time given the problem’s NP-hard nature. A benchmark with the branch-and-bound algorithm shows the modified ant colony optimization algorithm is suitable for large-case instances. Lastly, a sensitivity analysis on valuable fraction reveals the existence of a breakeven point that results in potential losses if not considered.